Case Report: Role of Ketone Monitoring in Diabetic Ketoacidosis With Acute Kidney Injury: Better Safe Than Sorry - Tinti, Davide; Savastio, Silvia; Peruzzi, Licia; De Sanctis, Luisa; Rabbone, Ivana (Frontiers in Pediatrics, 2022)
Background: Type 1 Diabetes (T1D) is a well-known endocrinological disease in children and adolescents characterized by immune-mediated destruction of pancreatic β-cells, leading to partial or total insulin deficiency, with an onset that can be subtle (polydipsia, polyuria, weight loss) or abrupt (Diabetic Keto-Acidosis, DKA or, although rarely, Hyperosmolar Hyperglycemic State, HHS). Severe DKA risk at the onset of T1D has recently significantly increased during the Sars-Cov2 pandemic with life-threatening complications often due to its management. DKA is marked by low pH (<7.3) and bicarbonates (< 15 mmol/L), in the presence of ketone bodies in plasma or urine, while HHS has normal pH (>7.3) and bicarbonates (> 15 mmol/L), with no or very low ketone bodies. Despite this, ketone monitoring is not universally available, and DKA diagnosis is mainly based on pH and bicarbonates. A proper diagnosis of the right form with main elements (pH, bicarbonates, ketones) is essential to begin the right treatment and to identify organ damage (such as acute kidney injury). Case presentations: In this series, we describe 3 case reports in which the onset of T1D was abrupt with severe acidosis (pH < 7.1) in the absence of both DKA and HHS. In a further evaluation, all 3 patients showed acute kidney injury, which caused low bicarbonates and severe acidosis without increasing ketone bodies. Conclusion: Even if it is not routinely recommended, a proper treatment including bicarbonates was then started, with a good response in terms of clinical and laboratory values. With this case series, we would like to encourage emergency physicians to monitor ketones, which are diriment for a proper diagnosis and treatment of DKA.